Morbidity Caused by Accidents in Children under Five Years - Mariela Dorta Figueredo; Mabel Godo González; Carlos Alberto Castellón González; Alina Esther González Hermida; Myleidis Portal Amador; Innerys Rosell García (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2013)
Background: Accidents or unintentional injuries are a global health problem. In addition, they are considered as one of the leading causes of morbidity in children. Objective: To describe the morbidity caused by accidents in children under the age of five years in the V Health Area in Cienfuegos. Methods: A descriptive study was conducted in Area V Polyclinic, Cienfuegos, aimed at analyzing the morbidity caused by accidents (from June to November 2008) in children from zero to five years who belonged to consultations 3, 4, 23 and 25 of that health area. The demographic variables, type of accident, cause, place of occurrence, adult presence at the time of the accident, request for medical assistance, as well as risk factors were analyzed. Results: 40.2% of the population studied had accidents and the accident frequency rate reached 48.2%. Children aged two, three and less than one year were the most affected as well as males. Falls, burns and foreign body aspiration were the most frequent accidents, occurring mostly at home. Conclusions: Unfortunately adults are not doing everything possible to reduce the occurrence of accidents. They need to be more active in the child vigilance and the elimination of potential triggering factors of the accident.